Public Debt and Economic Growth in Colombia: An Approach to Overlapping Generations - Mesa, Fernando; Sánchez, Germán; Zarta, Álvaro (Revista de Relaciones Internacionales, Estrategia y Seguridad, 2007)
With a selective reference is pointed out how the domestic and external public debt affects the saving decisions and the financial markets through the optimum tax policy. After that the behaviour of the domestic and external public debt and also the external private debt is studied through the data. The roll of the Colombian pension fond to finance the public deficit is explained. An overlapping generation model is constructed with the most important Colombian stylized facts. The theoretical model is calibrated for 12 generations, 12 periods each one of 5 years. The labour life of the individuals is ten periods and the pension periods are two. The behaviour of the household economies and productive sector are studied with respect to the previous assumptions. The labour productivity, both by experience and between generations, is estimated in order to calibrate the model. The public and private debt and economic growth simulations are conducted with the Colombian parameters in 2005. The simulations are realized changing: i) the total factor productivity; ii) external interest rate; and iii) the public expenditure.